2000
DOI: 10.1016/s0895-4356(00)00204-3
|View full text |Cite
|
Sign up to set email alerts
|

Which chronic conditions are associated with better or poorer quality of life?

Abstract: The objective of the present study is to compare the QL of a wide range of chronic disease patients. Secondary analysis of eight existing data sets, including over 15,000 patients, was performed. The studies were conducted between 1993 and 1996 and included population-based samples, referred samples, consecutive samples, and/or consecutive samples. The SF-36 or SF-24 were employed as generic QL instruments. Patients who were older, female, had a low level of education, were not living with a partner, and had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
359
4
47

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(448 citation statements)
references
References 27 publications
38
359
4
47
Order By: Relevance
“…They were compared with patients prior to primary hip arthroplasty, who had a mean PCS score of 29.0 and with chronic obstructive pulmonary disease, with a mean PCS score of 33.9. Sprangers et al [41] similarly reported that the majority of studied disease clusters were associated with physical and mental dysfunction; in particular, a profound physical impairment for musculoskeletal conditions in general. Compared to these findings, our groups of previously treated scoliosis patients, with a mean PCS score of 49, can be considered to have a near normal function, even though 4 out of 262 exhibited severe disability due to physical limitations from their spinal disorder.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They were compared with patients prior to primary hip arthroplasty, who had a mean PCS score of 29.0 and with chronic obstructive pulmonary disease, with a mean PCS score of 33.9. Sprangers et al [41] similarly reported that the majority of studied disease clusters were associated with physical and mental dysfunction; in particular, a profound physical impairment for musculoskeletal conditions in general. Compared to these findings, our groups of previously treated scoliosis patients, with a mean PCS score of 49, can be considered to have a near normal function, even though 4 out of 262 exhibited severe disability due to physical limitations from their spinal disorder.…”
Section: Discussionmentioning
confidence: 95%
“…There were no differences found between the groups in any of the other subscales. (PF Physical Functioning, RP Role Physical, BP Bodily Pain, GH General Health, VT Vitality, SF Social Functioning, RE Role Emotional, MH Mental Health) Table 6 Self-esteem and social activity in 262 patients with adolescent idiopathic scoliosis and 100 healthy controls from the SRS/MODEM'S instrument for outcome of scoliosis treatment [2] P-value (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), when the pain is the main problem and affects many activities; 4. crippled patients (61-80), when the back impinges on all aspects of the patient's life; and 5. score 81-100, patients are either bed-bound or exaggerating the symptoms (P=0.0007). Approximately 25% of each treatment group thought that their teenage period had been "ruined", over 30% of the patients had stopped all their spare time activities and over 40% thought they had become limited in their contacts with the opposite sex because of the treatment programme.…”
Section: Impression Of the Treatment Periodmentioning
confidence: 99%
“…Most studies that have found a relationship between other chronic conditions and poorer self-reported health status have looked at these relationships either by examining a list of specific conditions or by considering the number of chronic conditions overall (16,17,23,42,43). This study examined chronic conditions by considering the onset frequency of broad types of conditions over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Having arthritis has consistently been shown to be associated with poor SRH (4,22,23,37,42,43). Functional limitations associated with musculoskeletal conditions have also been associated with poorer health status (21)(22)(23)42,43). Previous cross-sectional studies examining the independent effects of several conditions have shown arthritis, and musculoskeletal symptoms generally, to be among the conditions with the strongest associations with reporting poor SRH (23,42).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation